PERAN GURU PENDIDIKAN AGAMA ISLAM DALAM MENUMBUHKAN SIKAP TOLERANSI PADA SISWA DI SMA NEGERI 14 KOTA MAKASSAR - Muh. Hidayat; Muhammad Izul Islam (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study examines the role of Islamic Religious Education (PAI) teachers in fostering students' tolerance attitudes at SMA Negeri 14 Makassar, a public senior high school characterized by religious diversity among its student body, comprising Muslim, Catholic, and Christian students. The research was motivated by national data indicating persistent intolerance incidents in Indonesian schools and the strategic position of PAI as an instrument for instilling inclusive and moderate religious values. This study employed a qualitative case study approach with a phenomenological perspective, involving the vice-principal for student affairs, a PAI teacher, and students as key informants. Data were collected through participatory observation, in-depth interviews, and documentation studies, then analyzed thematically through data reduction, data display, and conclusion drawing verified by triangulation. The findings show that students' tolerance attitudes have developed positively, reflected in mutual respect for religious, ethnic, and opinion differences, and in harmonious social relationships among students and between students and teachers. PAI teachers perform four interrelated roles, namely educator, motivator, instructor, and exemplar, in cultivating tolerance, grounded in the Islamic principle of rahmatan lil 'alamin while maintaining the doctrinal boundary between faith (aqidah) and social interaction (mu'amalah). Supporting factors include teacher competence, exemplary conduct, structured religious habituation programs, and school policies accommodating religious diversity, while inhibiting factors are largely technical, such as limited instructional time and varying student characters. This study contributes to the development of a contextual, teacher-centered model of tolerance education within Islamic Religious Education at the senior secondary level, particularly in schools with plural religious composition.